A Preliminary Study on the Effectiveness of "Clinical Situation Teaching" Course. - Tien, P. Y.; Wang, W. H.; Lee, M. S. (Tzu Chi Nursing Journal, 2026)
This study explores the effectiveness of the "Case method" combined with "Humanoid Diagram" in the "Clinical Scenario Teaching" students of a Nursing Department. The Case method involves the use of real clinical cases to engage students in discussions, aiming to enhance their critical thinking and problem-solving skills. The Humanoid Diagram Teaching method employs graphical representations of patient conditions, emphasizing patient-centered holistic care and fostering students' logical thinking and comprehensive understanding. Utilizing a qualitative research design, this study involved 47 students enrolled in the "Clinical Scenario Teaching " course at a university of science and technology in Eastern Taiwan. The study integrated both teaching methods into the classroom setting; incorporating group discussions and role-playing activities to help students effectively apply these approaches. The findings indicate that the Case method significantly bridges the gap between theoretical knowledge and clinical practice. It allows students to preemptively understand clinical health issues and appropriate interventions, thereby enhancing their critical thinking and problem-solving abilities. Students reported that this approach deepens their learning and aids in knowledge retention. On the other hand, the Humanoid Diagram Teaching method was found to promote teamwork and communication, improve students' grasp of the overall patient condition, and enhance their logical reasoning skills. By using humanoid diagrams, students can intuitively grasp the holistic health status of patients and learn to apply nursing knowledge in real-world scenarios. The study suggests that future curriculum development should integrate these two teaching methods to better connect academic learning with clinical practice, thereby fostering nursing professionals who possess a holistic perspective.